Consideration of pelvic tilt at the time of preoperative planning improves standing acetabular position after robotic-arm assisted total hip arthroplasty. Issue 1 (January 2023) - Hepinstall, Matthew S; Coden, Gloria; Salem, Hytham S; Naylor, Brandon; Matzko, Chelsea; Mont, Michael A
Introduction: Approximately half of dislocating total hip arthroplasties (THAs) demonstrate acetabular component position within traditional safe zones. It is unclear if postoperative functional acetabular position can be reliably improved by considering preoperative pelvic tilt. We investigated whether standing cup position targets could be more accurately achieved by considering preoperative standing pelvic tilt in addition to bone landmarks when planning for robot-assisted THA. Methods: We reviewed 146 THAs performed by a single surgeon using computed tomography-based 3-dimensional planning and robotic technology to guide acetabular reaming and component insertion. Planning for 73 consecutive cases started at 40° of inclination and 22° of anteversion relative to the supine functional plane and was adjusted to better match native hip anatomy. Planning for the next 73 cases was modified to consider standing pelvic position based on standing preoperative radiographs. We compared groups to determine the rate when cups were placed outside our standing targets of 15–30° anteversion and 35–50° inclination. Results: Cup position proved to be reliable in both groups, with 83% of cups in the anatomic planning cohort and 90% of cups in the functional planning cohort achieving standing targets for both anteversion and inclination ( p  = 0.227). Variances were lower in the functional planning group: 9.4° versus 15.8° of inclination ( p  = 0.079) and 18.3° versus 26.1° of anteversion ( p  = 0.352). The range of functional positions was narrower in the functional planning group: 35.7–47.5° versus 31.8–54.9° of inclination and 16.7–35.0° versus 10.1–35.9° of anteversion. Discussion: Our results suggest enhanced planning that considers pelvic tilt, when coupled to a precision tool to achieve the plan, can reliably achieve target standing component positions. Considering preoperative functional pelvic position may improve postoperative functional acetabular component placement in THA, but the clinical benefit of this has yet to be confirmed.